Profiling lifetime episodes of upper gastrointestinal bleeding among patients from rural Sub-Saharan Africa where schistosoma mansoni is endemic - Opio, Christopher Kenneth; Kazibwe, Francis; Ocama, Ponsiano; Rejani, Lalitha; Nikolaevna Belousova, Elena; Ajal, Paul (The Pan African Medical Journal, 2016)
Severe chronic hepatic schistosomiasis is a common cause of episodes upper gastrointestinal bleeding (UGIB) in sub-Saharan Africa (SSA). However, there is paucity of data on clinical epidemiology of episodes of UGIB from rural Africa despite on going public health interventions to control and eliminate schistosomiasis. Methods: Through a cross sectional study we profiled lifetime episodes of upper gastrointestinal bleeding and associated factors at a rural primary health facility in sub-Saharan Africa were schistosomiasis is endemic. The main outcome was number of lifetime episodes of UGIB analyzed as count data. Results: From 107 enrolled participants, 323 lifetime episodes of UGIB were reported. Fifty-seven percent experienced ≥ 2 lifetime episodes of UGIB. Ninety-four percent had severe chronic hepatic schistosomiasis and 80% esophageal varices. Alcohol use and viral hepatitis was infrequent. Eighty-eight percent were previously treated with praziquantel and 70% had a history of blood transfusion. No patient had ever had an endoscopy or treatment for prevention of recurrent variceal bleeding. Multivariable analysis identified a cluster of eight clinical factor variables (age ≥ 40, female sex, history of blood transfusion, abdominal collaterals, esophageal varices, pattern x periportal fibrosis, anemia, and thrombocytopenia) significantly associated (P-value < 0.05) with increased probability of experiencing two or more lifetime episodes of UGIB in our study. Conclusion: Upper gastrointestinal bleeding is a common health problem in this part of rural SSA where schistosomiasis is endemic. The clinical profile described is unique and is important for improved case management, and for future research.
Keywords: Upper gastrointestinal bleeding; Sub-Saharan Africa; Hepatic schistososomiasis